THE EFFECT OF LEADER EMOTIONAL INTELLIGENCE ON JOB PERFORMANCE THROUGH TRUST IN SUPERVISOR - RISKA ANANDA KONO; SETIA TJAHYANTI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
The purpose of this study is to determine what variables can affect Job Performance, There are several variables studied, namely Transformational Leadership, Transactional Leadership, Leader Emotional Intelligence and the mediation variable Trust In Supervisor. This study used 102 employees at Instansi XYZ, the research data was obtained from distribution to employees through a Likert Scale questionnaire.